SiC polytypes and doping nature effects on electrical properties of ZnO-SiC Schottky diodes - Rebaoui, Z.; Bouiajra, W.B.; Abboun Abid, M.; Saidane, A.; Jameel, D.; Henini, M.; Felix, J.F. (Elsevier, 2017)
Electrical properties of ZnO/SiC Schottky diodes with two SiC polytypes and N and P doping are investigated. Characterization was performed through I–V and C–V–f measurements. Schottky barrier height (Φb), ideality factor (n), and series resistance (Rs) were extracted from forward I–V characteristics. (Φb), carrier’s concentrations (Nd-Na) and (Rs) frequency dependence were extracted from C–V–f characteristics. The extracted n values suggest that current transport is dominated by interface generation-recombination and/or barrier tunneling mechanisms. When changing SiC polytypes, the rectifying ratio of ZnO/n-4HSiC is found to be twice that of ZnO/n-6HSiC. A change in doping nature gave a leakage current ratio of 40 between ZnO/p-4HSiC and ZnO/n- 4HSiC. These results indicate that ZnO/p-4HSiC diodes have a complex current transport compared to diodes on n-type SiC. From I-V measurements, barrier height values are 0.63eV, 0.65eV and 0.71 eV for heterojunction grown on n-6HSiC, n-4HSiC and p-4HSiC, respectively. C-V measurements gave higher values indicating the importance of interface density of states. Nss values at 1MHz frequency are 4.54×1011 eV-1 cm-2, 3×1012 eV-1 cm-2 and 8.13×1010 eV-1 cm-2 for ZnO/n-6HSiC, ZnO/n-4HSiC and ZnO/p-4HSiC, respectively. Results indicate the importance of SiC polytypes and its doping nature